154 Blocking the IL-1RI Co-receptor TILRR Reduces Vascular Inflammation – in vivo Analysis Using TILRR Knockout Mice. (31st May 2014) - Samokhin, Andriy; Francis, Sheila; Qwarnstrom, Eva
Abstract : Introduction: The toll-like and IL-1 receptor regulator (TILRR) is a co-receptor that binds the type I IL-1 signalling receptor (IL-1RI), and enhances signal amplification at the level of the receptor complex. 1–3 IL-1 is a pro-inflammatory cytokine, central to development of vascular diseases. Initial experiments demonstrated high levels of TILRR expression in atherosclerotic plaques in human vessels. In this study we evaluate the role of TILRR in development of atherosclerosis, and in vascular remodelling following carotid artery ligation using a TILRR knockout mice. Methods and results: Initial histological analysis of major organs from TILRR-/- mice demonstrated the same morphology as in tissues from wild type mice. To assess the role of TILRR on vascular repair TILRR-/- mice were used in a model of carotid artery ligation, and neointima formation and smooth muscle cell proliferation were assessed up to 4 weeks. Immunostaining of serial cross sections demonstrated high expression levels of TILRR in the area of ligation. TILRR knockout caused a decrease in neointima size by 48%, and about a 50% reduction in intima/media ratio after 4 weeks of ligation. Further, the number of smooth muscle cells in the neointima and medial area corresponded to 56% of level in wild type mice. To evaluate the role of TILRR in atherosclerosis, ApoE-/- mice we kept on a high fat diet for 8 weeks and injected with a peptide antibody directed against the TILRR functional site (i.v. 130ng/kg; twice a week). Immunohistochemical analysis of lesions from ApoE-/- mice revealed extensive expression of TILRR in atherosclerotic plaques. TILRR-antibody treatment resulted in reduction of plaque size in the aortic root by 28% and in the brachiocephalic artery by 40%. In addition, blocking TILRR function resulted in a two-fold increase in collagen content and a four-fold increase in SMC content of the lesions, characteristic of more stable plaques. TILRR-antibody treatment also reduced the number of elastin fibre breaks in the media and the number of buried fibrous caps within the plaques by about 60%. FACS analysis of blood demonstrated a reduction in inflammatory (Gr1-positive) monocytes by about 30%, known to be the major source of macrophages in plaques, and revealed a corresponding increase in the non-inflammatory phenotype. Conclusion: The data demonstrate a role for TILRR control in in vivo models of vascular disease, with effects on blood vessel response to injury and on development of atherosclerosis, and are consistent with TILRR control of IL-1RI function and with reduced inflammatory responses in the TILRR KO mice. Supported by the British Heart Foundation. References: Zhang X, et al . J Biol Chem 2010;285(10):7222–7232 Zhang X, et al . J Biol Chem 2012;287:12348–12352 Hudson RC, et al . MDPI Biology 2012;1:484–494